Zastosowanie elementów metody Marii Montessori w tradycyjnym przedszkolu. Refl eksja nad badaniami w działaniu z pozycji zewnętrznego obserwatora - Kamila Zdanowicz-Kucharczyk (Problemy Wczesnej Edukacji)
In this text I present, from the perspective of an external observer, research which shows, how using the Maria Montessori method helps teachers to work with children individually. The research method, which is action research, makes it possible to observe how the researcher-teacher involves children in all activities and enhances their self-esteem. At the same time the teacher`s engagement, independence and creativity become active while using the Maria Montessori method. I also present diffi culties, which could happen, when the Maria Montessori method is used in the traditional kindergarten.